The Impact of Supply Chain Management Approaches on Supply Chain Performance in Iraq - Jamal Ahmed Al-Doori (International Journal of Supply Chain Management, 2018)
Indeed due to globalization and changing regional powers, supply chain (SC) has become an essential element. It is evident that political, social and economic changes over the few past decades become supply chain more uncertain and complex. The economy of Iraq is dominated by Oil that is contributing 95% in its foreign exchange. Meanwhile, War has destroyed its major infrastructure still supply is moving on but with more uncertainty. AlthoughWar destroyed the economy badly. However, there are numerous ways to reduce the uncertainty that will improve the performance; supply chain management (SCM) approaches cannot be neglected. Whereas, supply chain management approaches have determined the performance in various industries and in various regions. The aim of this study to explore the potential benefits of supply chain management approaches toward attaining supply chain performance. This is an empirical investigation conducting among members of oil and gas supply chain in Iraq. Data were collected from 260 members of thesupply chain that include drilling, processing, distribution areas of Iraq. Factor analysis and multiple regressions through SPSS have been used for data analysis. The finding of this study reveals that all three supply chain management approaches information sharing (IS), joint decision making (JDM) and risk and reward sharing (RRS) positively and significantly affect the supply chain performance.